Final irrigation with bioglass solution in regenerative endodontic procedure induces tissue formation inside the root canals, collagen maturation, proliferation cell and presence of osteocalcin - de Paula, Kiani dos Santos; dos Reis-Prado, Alexandre Henrique; de Jesus, Witalo Pereira; Goto, Juliana [UNESP]; de Arantes, Lara Cancella; Verçosa, Marina; Cintra, Luciano Tavares Angelo [UNESP]; Ervolino, Edilson [UNESP]; Szawka, Raphael Escorsim; Crovace, Murilo Camuri; de Mesquita, Ricardo Alves; Benetti, Francine (Wiley, 2024)
Aim: To evaluate the influence of an experimental solution of cobalt-doped F18 bioactive glass (F18Co) on tissue repair following regenerative endodontic procedure (REP) in rat molars. Methodology: The F18Co solution was prepared at a ratio of 1:5 F18Co powder to distilled water. The right or left upper first molars of 12 Wistar rats were used, where the pulps were exposed, removed, and irrigated with 2.5% sodium hypochlorite (NaOCl), followed by 17% ethylenediaminetetraacetic acid (EDTA) (5 min each). Subsequently, the molars were divided into two groups (n = 6): REP-SS and REP-F18Co, where they received a final irrigation (5 min) with saline solution (SS) or F18Co solution, respectively. Then, intracanal bleeding was induced, and the tooth was sealed. Untreated molars were used as controls (n = 3). At 21 days, the rats were euthanized, and the specimens were processed for analysis of mineralized tissue and soft tissue formation inside the root canal using haematoxylin-eosin. The presence and maturation of collagen were evaluated by Masson's trichrome and picrosirius red staining. Immunolabelling analyses of proliferating cell nuclear antigen (PCNA) and osteocalcin (OCN) were performed. The data were submitted to the Mann–Whitney U-test (p <.05). Results: There was a similar formation of mineralized tissue in thickness and length in REP-SS and REP-F18Co groups (p >.05). Regarding the presence of newly formed soft tissue, most specimens of the REP-F18Co had tissue formation up to the cervical third of the canal, whilst the REP-SS specimens showed formation up to the middle third (p <.05), and there was higher maturation of collagen in REP-F18Co (p <.05). The number of PCNA-positive cells found in the apical third of the root canal was significantly higher in the F18Co group, as well as the OCN immunolabelling, which was severe in most specimens of REP-F18Co, and low in most specimens of REP-SS. Conclusion: The final irrigation with F18Co bioactive glass solution in REP did not influence mineralized tissue formation but induced soft tissue formation inside the root canals, with higher collagen maturation, and an increase in PCNA-positive cells and OCN immunolabelling.
Keywords: bioactive glass; biocompatibility; osteocalcin; PCNA; regenerative endodontic procedure